2014
DOI: 10.2217/imt.14.63
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Based-immunotherapy Against Allergy

Abstract: Allergic diseases are one of the most prevalent diseases, reaching epidemic proportions in developed countries. An allergic reaction occurs after contact with an environmental protein, such as inhalants allergens (pollen, animal dander, house dust mites), or food proteins. This response is known as part of the type 2 immunity that is counterbalanced by Type 1 immunity and Tregs. Widely used allergen-specific immunotherapy (IT) is a long term treatment to induce such switch from Th2 to Th1 response. However, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 78 publications
0
39
0
3
Order By: Relevance
“…In recent years, nanotechnologies have strongly emerged in vaccinology and, more currently, in the allergen immunotherapy field, with several studies in animals showing very promising future perspectives. 35,87 Of particular interest in this field is how nanocarrier/allergen complexes can be formulated to obtain improved stability, slow release kinetics, selective targeting of specific immune cells, and …”
Section: Resultsmentioning
confidence: 99%
“…In recent years, nanotechnologies have strongly emerged in vaccinology and, more currently, in the allergen immunotherapy field, with several studies in animals showing very promising future perspectives. 35,87 Of particular interest in this field is how nanocarrier/allergen complexes can be formulated to obtain improved stability, slow release kinetics, selective targeting of specific immune cells, and …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it has also been shown that PEG can change the adhesion properties between nanoparticles and mucin fibers in mucosal tissues, and as a result may enhance their penetration through layers of sublingual mucosa. 23,24 As of today, none of the commercially available SLIT vaccines contain any adjuvants. 25 However, a few studies have shown positive results in murine SLIT models using positively charged maltodextrin and chitosan based microparticles as antigen carriers for mucosal vaccination, where the immune response was enhanced through DC targeting.…”
mentioning
confidence: 99%
“…A imunoterapia de mucosa utilizando probióticos apresenta--se como uma boa estratégia para o tratamento de doenças alérgicas (Ganesh and Versalovic, 2015;Smits et al, 2016). Por isso, neste estudo, nós avaliamos os efeitos imunomoduladores da administração oral de L. lactis NCDO2118 expressando Hsp65 de M. leprae no tratamento da asma experimental.…”
Section: Discussionunclassified
“…Em conjunto, as citocinas e os mediadores inflamatórios contribuem para o desenvolvimento das principais fisiopatologias da asma, como a inflamação eosinofílica, hipersecreção de muco, obstrução e hiper--reatividade das vias aéreas (Heijink and Van Oosterhout, 2006;Gamazo et al, 2014).…”
Section: Resposta Imunológica Na Asma E Imunoterapiasunclassified
See 1 more Smart Citation